ETR 300 : Perfume House / Nor Lizawati Desa ... [et al.] - Desa, Nor Lizawati; Muhamad, Nurul Hasliza; Mohd Sharif Marikan, Azana Marikan; Abdul Razak, Hartini (2002)
Perfume House, as retailer business provides a variety of perfume directly to the customers. This business is registered under partnership agreement. We involved in this business because as we survey, Bumiputera has no intention to organize this business. So, we as a new entrepreneur take this chance to run our business. We choose 'Perfume House' as our business name is because the word 'perfume' itself show that we sell a perfume. While the word 'house' shows that our shop provide a variety of perfumes. Our business situated at G-01 ,Prangin Mall, Jalan Dr. Lim Chwee Leong, 11000 Penang. This location has been chosen because Prang in Mall is located at the center of Georgetown City and this made Prangin Mall as a famous shopping complex in Penang compared to another shopping complex. Besides that, transportation and communication system available will make customers easy to come to our outlet. So we take this advantage to run this business besides increase our profit.